The effectiveness of remote delivered intervention for loneliness reduction in older adults: A systematic review and meta-analysis - Fu, Zhengke; Yan, Mengsi; Meng, Chao (Frontiers in Psychology, 2022)
Background: Remote delivered intervention is widely applied to loneliness treatment in older adults, but the effect is controversial. This study aimed to evaluate the effects of remote delivered intervention on loneliness using a systematic review and meta-analysis. Methods: The PubMed, the Cochrane Central Register of Controlled Trials, EMBASE, CINAHL (EBSCO), PsycINFO (EBSCO) database were searched for studies published through 7 July 2021. Thirteen randomized controlled trials of remote delivered intervention compared with usual care, brief contact, or no intervention for loneliness were included. A random effects model measured estimation of loneliness reduction. Furthermore, standardized mean differences (SMDs), 95% confidence intervals (CIs), publication bias, and heterogeneity were calculated. Subgroup analysis was used to explore the factors that might affect the treatment effects. Results: The evidence of remote delivered intervention on loneliness reduction was certain (SMD = -0.41 [95% CI, -0.70 to -0.13]). Media subgroup analysis supported the effectiveness of intervention delivered by video call (SMD = -0.54 [95% CI, -0.83 to -0.25]); treatment strategy subgroup analysis found evidence to support the effectiveness of increasing social support and maladaptive social cognition treatment strategy (SMD = -0.47 [95% CI, -0.77 to -0.18] and SMD = -1.04 [95% CI, -1.98 to -0.10], respectively); participants subgroup analysis shown the effectiveness of intervention for older adults living in LTC and social isolation (SMD = -1.40 [95% CI, -2.43 to -0.36] and SMD = -0.55 [95% CI, -0.74 to -0.36], respectively); group format subgroup analysis testified the effectiveness of intervention carried out in individual format (SMD = -0.39 [95% CI, -0.71 to -0.07]); measurement time points subgroup analysis found the positive effect of intervention at three months and three to six months stage (SMD = -0.33 [95% CI, -0.52 to -0.14] and SMD = -0.32 [95% CI, -0.57 to -0.07], respectively). Significant publication bias was detected (p < .05), and the heterogeneity of the studies was substantial. Conclusions: This systematic review and meta-analysis demonstrates that remote delivered intervention can reduce loneliness in older adults, and it appears to be affected by media type, treatment strategy, participants characteristics, group format, and measurement time points.